In vitro assessment of Pediococcus acidilactici Kp10 for its potential use in the food industry - Abbasiliasi, Sahar; Tan, Joo Shun; Bashokouh, Fatemeh; Tengku Ibrahim, Tengku Azmi; Mustafa, Shuhaimi; Vakhshiteh, Faezeh; Sivasamboo, Subhashini; Ariff, Arbakariya (BioMed Central, 2017)
Background: Selection of a microbial strain for the incorporation into food products requires in vitro and in vivo evaluations. A bacteriocin-producing lactic acid bacterium (LAB), Pediococcus acidilactici Kp10, isolated from a traditional dried curd was assessed in vitro for its beneficial properties as a potential probiotic and starter culture. The inhibitory spectra of the bacterial strain against different gram-positive and gram-negative bacteria, its cell surface hydrophobicity and resistance to phenol, its haemolytic, amylolytic and proteolytic activities, ability to produce acid and coagulate milk together with its enzymatic characteristics and adhesion property were all evaluated in vitro. Results: P. acidilactici Kp10 was moderately tolerant to phenol and adhere to mammalian epithelial cells (Vero cells and ileal mucosal epithelium). The bacterium also exhibited antimicrobial activity against several gram-positive and gram-negative food-spoilage and food-borne pathogens such as Listeria monocytgenes ATCC 15313, Salmonella enterica ATCC 13311, Shigella sonnei ATCC 9290, Klebsiella oxytoca ATCC 13182, Enterobacter cloaca ATCC 35030 and Streptococcus pyogenes ATCC 12378. The absence of haemolytic activity and proteinase (trypsin) and the presence of a strong peptidase (leucine-arylamidase) and esterase-lipase (C4 and C8) were observed in this LAB strain. P. acidilactici Kp10 also produced acid, coagulated milk and has demonstrated proteolytic and amylolactic activities. Conclusion: The properties exhibited by P. acidilactici Kp10 suggested its potential application as probiotic and starter culture in the food industry.